(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The study shows results of research on heavy metals concentration in biomass of common reed, hemp and Reed canary grass. The research of common reed was performed during winter period from 2010 until 2012 in 11 natural and artificial water bodies of Latvia. For the harvested biomass in the spring of 2009 and 2010, hemp and reed canary grass samples were investigated.For the collected common reed samples the heavy metal content (Cd, Pb, Cu, Ni, Fe) was established in the biomass. For the hemp and reed canary grass samples, Cd and Pb content were established in the biomass. On the basis of the findings of this research, the suitability of the plant biomass for energy production was analyzed.The heavy metal content in the common reed biomass is suitable for the requirements of solid biofuel. Common reed from all the reed beds of the Latgale (region of Latvia) can be collected in one place and used for the production of fuel. The removal of common reed will help to reduce the heavy metal content in the natural waters and sediment of the reed beds.In the hemp and reed canary grass samples the heavy metals were ascertained periodically. It was found that in some of the research samples they exceeded the MAC for fuel.